Extreme isotopic variations in Heard Island lavas and the nature of mantle reservoirs - Barling, J; Goldstein, S (1990)
OCEANIC basalts are produced by melting of the Earth's mantle and are widely used to probe its composition. The observation of systematic, coupled variations in the neodymium, strontium and lead isotopic compositions of these basalts1 has been widely interpreted as reflecting the mixing of identifiable mantle components. White2 and Zindler and Hart3 have suggested that the isotopic compositions of mid-ocean-ridge and ocean island basalts (MORB and OIB) can be considered as mixtures of a depleted MORB-type mantle component with a few other components reflecting long-term enrichment of Rb/Sr, Nd/Sm and/or U/Pb ratios. It remains unclear whether these components should be considered as hypothetical mixing endmembers, or whether they exist physically as mantle reservoirs. This question may be addressed if the mixing endmembers of individual mantle plumes can be identified. To this end, we report linear Pb-Pb and curvilinear Pb-Nd and Pb-Sr isotopic covariations in Recent lavas of Heard Island, southern Indian Ocean, indicating binary mixing. The hyperbolic relationships are unique among oceanic basalts and tightly constrain the isotopic compositions of the plume source components, which do not coincide with the mantle endmember components of réf. 3. If our results are generally applicable to other plumes, they call into question the existence of large mantle reservoirs corresponding to these components, and indicate that actual oceanic basalt source reservoirs have intermediate isotopic compositions.